2011
DOI: 10.1097/cad.0b013e328344ac68
|View full text |Cite
|
Sign up to set email alerts
|

YM155, a novel survivin suppressant, enhances taxane-induced apoptosis and tumor regression in a human Calu 6 lung cancer xenograft model

Abstract: Survivin, an apoptotic inhibitor, is overexpressed in the majority of human tumor types and represents a novel target for anticancer therapy. Taxanes induce a mitotic cell-cycle block through the inhibition of microtubule depolymerization, with subsequent elevated expression/stabilization of survivin. We investigated the administration of survivin suppressant YM155 monobromide (YM155), in combination with docetaxel, in a human non-small-cell lung cancer (NSCLC) xenograft model. Animals received a 7-day continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 31 publications
(45 reference statements)
4
37
1
Order By: Relevance
“…Thus, we also tested the cytotoxic effects of YM155 combined with cisplatin, gemcitabine, or both. YM155 has been reported to potentiate the therapeutic effects of many chemotherapy or targeted-therapy agents (13,14,(35)(36)(37)(38)(39). However, our results demonstrated that YM155 alone exerted potent cytotoxicity in BFTC905 cells, and addition of cisplatin and/or gemcitabine to YM155 did not elicit synergistic or additive effects.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Thus, we also tested the cytotoxic effects of YM155 combined with cisplatin, gemcitabine, or both. YM155 has been reported to potentiate the therapeutic effects of many chemotherapy or targeted-therapy agents (13,14,(35)(36)(37)(38)(39). However, our results demonstrated that YM155 alone exerted potent cytotoxicity in BFTC905 cells, and addition of cisplatin and/or gemcitabine to YM155 did not elicit synergistic or additive effects.…”
Section: Discussioncontrasting
confidence: 53%
“…Sepantronium bromide, a small molecule also known as YM155, directly binds to the transcription factor ILF3/NF110 or disrupts ILF3/p54 nrb complex to inhibit the activity of survivin gene promoter (10,11). YM155 has been demonstrated to inhibit the progression of certain neoplasms, such as prostate (10,12) and lung cancer (13,14). In the present study, we demonstrated that gemcitabine-resistant human TCC BFTC905 cells were sensitive to YM155 at very low concentrations, and the antineoplastic effects were more potent than cisplatin and/or gemcitabine.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple combination studies with YM155 were conducted with paclitaxel or docetaxel regimens based on the rationale that YM155 may be able to overcome taxane-mediated upregulation of survivin expression, which promotes drug resistance (44,(48)(49)(50). However, the lack of efficacy that was observed in these clinical studies may have been due to incomplete suppression of survivin levels in the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In pre-clinical experiments, YM155 as a single agent downregulated the transcription of survivin in a dose/time-dependent manner, triggering p53-independent apoptosis in a wide range of human tumor cells. YM155 also induced tumor regression in established cancer xenografts (24,25), and the combination of YM155 with various chemotherapeutic agents potentiated apoptosis induction in several human cancers (26)(27)(28). Despite its demonstrated efficacy in targeting tumor cells, the effects of YM155 in combination with DNA-damaging drugs have remained largely unknown.…”
Section: Introductionmentioning
confidence: 99%